Protection against experimental aspergillosis by heat-killed yeast is not antibody dependent. (28th February 2014) - Clemons, Karl V.; Martinez, Marife; Chen, Vicky; Liu, Min; Yoon, Hee Jung; Stevens, David A.
Abstract : Previously we showed heat-killed yeast (HKY) of Saccharomyces cerevisiae administered as a vaccine are protective against systemic murine aspergillosis (and other mycoses) and that HKY induces antibody and cellular responses. To determine the role of antibodies in this protection, male antibody knockout mice (KO; strain B6.129S2- Igh-6 tm1Cgn /J) and C57BL/6 wild-type (WT) mice were vaccinated subcutaneously with 6 × 10 7 HKY or phosphate buffered saline (PBS) given three or four times. Mice were infected intravenously with 6 × 10 6 viable conidia of Aspergillus fumigatus 10AF and mortality tallied through 12 days post infection. HKY vaccination given four times proved protective in the prolongation of survival of WT and KO mice vs. the respective PBS-treated controls. In one study, survival was prolonged in vaccinated WT or KO mice ( P < 0.0001). A second study confirmed these results ( P < 0.0001). Additionally, a three-dose regimen of HKY was also effective, prolonging survival of WT or KO mice vs. controls ( P = 0.0002); no difference was found when the effectiveness of three- or four-dose regimens was compared. No significant differences in survival were found between HKY-vaccinated WT and KO mice, nor were PBS-treated KO mice more susceptible to infection than PBS-treated WT mice. Similar results were noted in another study in which a higher infectious inoculum and a three-dose regimen were used. Overall, antibodies do not appear to play a significant role in HKY-induced prolongation of survival in systemic aspergillosis, nor do antibodies appear to play a role in the innate resistance of the mice to aspergillosis.